Straightening the governance of Waqf using Tawhidic approaches / Dalila Daud and Rashidah Abdul Rahman - Daud, Dalila; Abdul Rahman, Rashidah (Academy of Contemporary Islamic Studies (ACIS), 2018)
Waqf has the quality of perpetuity so waqf properties cannot be sold, bought or given as a gift to others. Therefore, it is necessary to make sure that these properties are fully utilised and properly managed. In order to properly manage the properties, it is essential for the State Religious Councils (SRC) to have proper governance, which can be shown through waqf reporting. The purpose of this paper is to propose a model of waqf governance which includes the Tawhidic strategies in order to prevent attributes of non-reporting. The model shows the governance factors that may have contributed to the implementation of reporting in SRCs. A series of Islamic governance literature is discussed and explained to establish a model. The conceptual model shows the recommended strategies and attributes of reporting and how Tawhidic strategies can be implemented to solve the problem of insufficient transparency in reporting. This paper has offered a new and significant information, by proposing a new model in providing insight on how to improve in waqf reporting transparency.